Preparation of a porous Sn@C nanocomposite as a high-performance anode material for lithium-ion batteries. Issue 28 (29th June 2015) - Zhang, Yanjun; Jiang, Li; Wang, Chunru
Abstract : A porous Sn@C nanocomposite was prepared via a facile hydrothermal method combined with a simple post-calcination process. It exhibited excellent electrochemical behavior with a high reversible capacity, long cycle life and good rate capability when used as an anode material for lithium ion batteries. Abstract : A porous Sn@C nanocomposite was prepared via a facile hydrothermal method combined with a simple post-calcination process, using stannous octoate as the Sn source and glucose as the C source. The as-prepared Sn@C nanocomposite exhibited excellent electrochemical behavior with a high reversible capacity, long cycle life and good rate capability when used as an anode material for lithium ion batteries.